Identifying novel molecular mechanisms of healthspan using multi-omics - Smith, Meghan Elizabeth, author; LaRocca, Tom, advisor; Hamilton, Karyn, committee member; Broussard, Josiane, committee member; Ehrhart, Nicole, committee member (Colorado State University. Libraries, 2023)
An important goal in research on aging is to extend healthspan, the period of life spent healthy and disease-free. Next-generation sequencing and other emerging bioinformatics technologies (e.g., RNA-seq/transcriptomics, epigenetic profiling, and proteomics) have made it possible to broadly profile potential molecular mediators of aging, and perhaps identify therapeutic targets. The studies in this dissertation focus on using transcriptomics and complementary "multi-omics" strategies to characterize novel cellular mechanisms of aging, and to determine their relevance to systemic/functional health in humans. With the guidance of my mentoring team, I completed three studies in which I identified novel mediators of healthspan-related exercise training responsiveness, age-related inflammation, and cognitive/motor function decline in middle-aged and older adults. One particularly novel focus among these studies was the role of non-coding repetitive RNAs (derived from transposable elements) in healthspan. Transposable elements have been linked to known mechanisms of aging, and this topic is reviewed at the start of this dissertation to provide perspective on their role in the context of research on aging biology. Collectively, my findings represent new ideas for targetable genes and proteins that may influence human healthspan.
Keywords: healthspan; exercise; transcriptome